Subjectivity of Time Perception: A Visual Emotional Orchestration - Lambrechts, Anna; Mella, Nathalie M.; Pouthas, Viviane; Noulhiane, Marion (Frontiers in Integrative Neuroscience, 2011)
The aim of the present study was to examine how visual emotional content could orchestrate time perception. The experimental design allowed us to single out the share of emotion in the specific processing of content-bearing pictures, i.e., real-life scenes. Two groups of participants had to reproduce the duration (2, 4, or 6 s) of content-deprived stimuli (gray squares) or differentially valenced content-bearing stimuli, which included neutral, pleasant, and unpleasant pictures (International Affective Pictures Systems). Results showed that the effect of content differed according to duration: at 2 s, the reproduced duration was longer for content-bearing than content-deprived stimuli, but the difference between the two types of stimuli decreased as duration increased and was not significant for the longest duration (6 s). At 4 s, emotional (pleasant and unpleasant) stimuli were judged longer than neutral pictures. Furthermore, whatever the duration, the precision of the reproduction was greater for non-emotional than emotional stimuli (pleasant and unpleasant). These results suggest a dissociation within content effect on timing in the visual modality: relative overestimation of all content-bearing pictures limited to short durations (2 s), and delayed overestimation of emotional relative to neutral pictures at 4 s, as well as a lesser precision in the temporal judgment of emotional pictures whatever the duration. Our results underline the relevance for time perception models to integrate two ways of assessing timing in relationship with emotion: accuracy and precision.